Surveying borders, boundaries, and contested spaces in curriculum and pedagogy - Reilly, Cole; Russell, Victoria; Laurel K. Chehayl; Morna M. McDermott (Curriculum and pedagogy series., 2011)
The Curriculum and Pedagogy book series is an enactment of the mission and values espoused by the Curriculum and Pedagogy Group, an international educational organization serving those who share a common faith in democracy and a commitment to public moral leadership in schools and society. Accordingly, the mission of this series is to advance scholarship that engages critical dispositions towards curriculum and instruction, educational empowerment, individual and collectivized agency, and social justice. The purpose of the series is to create and nurture democratic spaces in education, an aspect of educational thought that is frequently lacking in the extant literature, often jettisoned via efforts to de-politicize the study of education. Rather than ignore these conversations, this series offers the capacity for educational renewal and social change through scholarly research, arts-based projects, social action, academic enrichment, and community engagement. Authors will evidence their commitment to the principles of democracy, transparency, agency, multicultural inclusion, ethnic diversity, gender and sexuality equity, economic justice, and international cooperation. Furthermore, these authors will contribute to the development of deeper critical insights into the historical, political, aesthetic, cultural, and institutional subtexts and contexts of curriculum that impact educational practices. Believing that curriculum studies and the ethical conduct that is congruent with such studies must become part of the fabric of public life and classroom practices, this book series brings together prose, poetry, and visual artistry from teachers, professors, graduate students, early childhood leaders, school administrators, curriculum workers and planners, museum and agency directors, curators, artists, and various under-represented groups in projects that interrogate curriculum and pedagogical theories.